(untitled) (Bangladesh Journal of Pharmacology, 2015)
The study aimed to determine the effect of tangeretin in inhibiting the interleukin-1β (IL-1β)-induced proliferation of RASFs and suppression of the production of inflammatory mediators. RASFs were isolated from synovial tissue obtained from patients with RA during knee arthroscopy. The cells were exposed to IL‑1β (1.0 ng/mL) and/ or tangeretin (50 or 100 µM). Cell viability was assessed following treatments. Expressions of MMPs and COX-2 were analysed by real-time PCR and Western blotting. Production of prostaglandin E2 (PGE2) by RASFs were analysed by ELISA. Expressions of mitogen activated protein kinases (MAPKs) and nuclear factor-kB (NF-kB) were assessed by western blotting. Tangeretin significantly inhibited the proliferation of RASFs, as well as down-regulated the expression of MMP-1, MMP-3 and COX-2 mRNA and protein and also the phosphorylation of ERK, p38 and JNK. Raised level of expression of NF-κB and PGE2 induced by IL-1β was reduced by tangeretin. Results indicate that tangeretin was effective in inhibiting the synovial fibroblast proliferation, as well regulated MMPs, COX-2, PGE2 via modulation of p38 MAPK, ERK and JNK pathways.